PROSES PEMANENAN HASIL TANAMAN UNTUK KECUKUPAN PANGAN MAHASANTRI PENGHAPAL AL QURAN DI YAYASAN LAYAR DAKWAH - Masdania Zurairah; Muhammad Fiza Lubis; Muhammad Fazri Pasaribu; Refiza, Refiza; Refiza4, Edi Syahputra Saragih (Bajang Institute, 2025)
The harvesting process for each plant is different according to the time. The harvesting process to achieve maximum results is carried out by maintenance, fertilization and watering. The harvesting process for chilies, tomatoes, eggplants, pumpkins, long beans, peanuts and cassava. Harvesting is done by pulling out such as peanuts, by pulling out plants with loose soil, the pulling process is very easy to do, so that it will produce peanuts in the soil. Likewise, cassava harvesting is done by pulling out or pulling the tree trunk until the cassava fruit is also pulled. Chilies, tomatoes, eggplants, long beans and pumpkins are harvested by picking them. The fastest harvest time is tomatoes 60 days. The longest time to harvest is cassava up to 240 days. With this post-harvest, it can meet the needs of students in food